2012
DOI: 10.1136/bcr-2012-007400
|View full text |Cite
|
Sign up to set email alerts
|

Malignant fibrous histiocytoma of the gingiva

Abstract: Malignant fibrous histiocytoma (MFH) is widely regarded as the commonest soft tissue sarcoma of adulthood which tends to occur in the deep soft tissues of the extremities and the retroperitoneum. Uncertain histogenesis and numerous subtypes make MFH a rather controversial entity. These tumours are relatively rare in the head and neck region accounting for only 1-3% of all cases of MFH. MFH exhibits a heterogenous histology of spindle cells in a characteristic storiform pattern with pleomorphic tumour cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The 11 considered patients were 5 females and 6 males, with a mean age of 50.8 years, and range between 20 and 82 years. Regarding the site of localization, gums were involved in 4 cases [32,33,36,40]; the tongue was affected in 3 patients, of which 2 cases concerned the lateral surface [19,41]; and the base of the tongue in one case [39]. In one case, the lesion manifested on the oral mucosa [34,35]; another case involved the palate [38] and one the floor of the mouth [43].…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The 11 considered patients were 5 females and 6 males, with a mean age of 50.8 years, and range between 20 and 82 years. Regarding the site of localization, gums were involved in 4 cases [32,33,36,40]; the tongue was affected in 3 patients, of which 2 cases concerned the lateral surface [19,41]; and the base of the tongue in one case [39]. In one case, the lesion manifested on the oral mucosa [34,35]; another case involved the palate [38] and one the floor of the mouth [43].…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Regarding histotype, 6 cases of histiocytoma presented a storiform-pleomorphic pattern [32,33,40,41,43], one study reported undifferentiated high-grade pleomorphic sarcoma [38], and another one myxoid variant [34] of histiocytoma, while in 3 studies [35,36,39], no specification of histologic subtype was reported. Immunohistochemical positivity for vimentin was reported in 6 studies [32,34,35,38,39,43]; in 5 of these, it was associated with positivity for CD68 [32,34,38,39,43]. Positivity for reticulin was revealed in one study [36], while in another, anti-α 1 -chymothrypsin and α-smooth muscle actin positivity [19] were detected.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…10 According to literature data, the most common soft tissue sarcoma in the head and neck area is rhabdomyosarcoma, followed by UPS, fibrosarcoma and neurogenic sarcoma. 11 Therefore, recently there are several reports of UPS in buccal mucosa, 12 gingiva, 13 and mandible with pathological fracture, 14 and one case of AFX in the mucosa of the floor of mouth in a patient after squamous cell carcinoma, treated with radiotherapy. 15 The lesion in the last case was superficial with a malignant, histiocytic morphology, thus a diagnosis of AFX to those authors seemed more appropriate than UPS.…”
Section: Discussionmentioning
confidence: 99%